The Effect of Differential Attentional Focus Strategies on the Performance of Military Elite Shooters - Amin Amini; Mohammad Vaezmousavi (Behavioural Neurology)
Background and Objective. The effect of attentional focus strategies on performance has been an interesting area of investigation, especially when the precision of performance is of significance. The purpose of the present study is to investigate the effect of different attentional focus strategies on performance precision of elite military shooters. Methods. This study is semiexperimental with an intragroup design. A number of 10 military marksmen (30-42 years old) with at least 10 years of experience in shooting performed under four attentional focus strategies in a counterbalanced design. In each strategy, two blocks (each consisting of 20 trials) were conducted. Shooters’ performance was recorded using SCATT device and analyzed using the factorial variance analysis with repeated measure. Results. Results showed that the interactional effects of internal-external/relevant-irrelevant focuses of attention were significant on shooting record, shooting accumulation, and stability on the target center. Results suggest that the external-relevant attentional focus strategies were more effective than other focus strategies. Conclusion. The results of the study support the hypothesis that external-relevant attentional focus produced better scores, better accumulation, more stability at the target center, and less average fluctuation. Therefore, this attentional focus strategy improves performance precision of military elite shooters.